Utility of the Platelet-to-Lymphocyte Ratio in Diagnosing and Predicting Treatment Success in Preterm Neonates with Patent Ductus Arteriosus. (15th April 2021) - Karabulut, Birol; Arcagök, Baran Cengiz; Simsek, Ayse
Abstract: Background: We investigated the predictive ability of the platelet-to-lymphocyte ratio (PLR) in preterm infants to discriminate those with and without hemodynamically significant PDA (hsPDA and non-hsPDA), hsPDA defined by those requiring medical intervention. Methods: This observational retrospective cohort study included premature neonates (<34 weeks gestational age) with routine complete blood counts in a neonatal intensive care unit. Results: PLR values on the 1st, 2nd, 3rd, and 7th days of birth were higher and lymphocyte counts were lower in the hsPDA than in the non-hsPDA group. Plateletcrit (PCT) values on the 2nd and 3rd days of birth were lower in the hsPDA group. All hsPDAs closed with medical therapy. Conclusions: PLR may be a supportive tool for predicting those preterm infants with PDAs requiring medical intervention. This may serve as a guide for future studies investigating the predictive value of PCT and PLR for hsPDA in preterm infants.